STUDY OF DNA TRANSFORMATION DYNAMICS IN ВНК-21/2-17 CELL CULTURE USING FLOW CYTOMETRY DURING FMD VIRUS REPRODUCTION - M. N. Guseva; M. A. Shevchenko; D. V. Mikhalishin; V. V. Mikhalishin; B. L. Manin (Ветеринария сегодня)
The research tasks covered the study of ВНК-21/2-17 cell DNA transformation dynamics during FMDV reproduction process. It was noted that the destruction of major cell population coincided with the increase in apoptotic cell number and detritus amount. Three hours post cell culture infection increase in apoptosis and detritus was observed, G 1-phase decreased by 17–21% and polynuclear cells grew by 2.3 times. In seven hours, the drastic rise in cell death was noted. It was established that at all stages of FMDV culture in ВНК-21/2-17 suspension cell line, diploid cells G1(2n) were predominant, being basic cells for the virus reproduction. Cells in synthetic (S) and G2and M-phases were less susceptible to virus. Using ﬂow cytometry technique made it possible to quantify cell cycle phases during reproduction in FMDV cells. We also succeeded in comparing between these phases, virus livability and virus reproduction dynamics. The study of FMDV cytopathic eﬀect in ВНК-21/2-17 cells demonstrated that one of the optimization trends in culture vaccine production include proliferation inhibitory factor use at a certain cell cycle phase.